Comprehensive comparative toxicity study on tomato (Solanum lycopersicum) and brinjal (Solanum melongena) using green labelled insecticides against Bemisia tabaci - T, ANIL KUMAR S; M, NIKHIL R; S, RAJNA; MAHAPATRO, G K (The Indian Journal of Agricultural Sciences, 2023)
Bemisia tabaci a serious sucking pest of tomato (Solanum lycopersicum L.) and brinjal (Solanum melongena L.), is mostly managed using high-dose conventional insecticides, which are harmful for end-users and the environment. Target-insect is also known to exhibit host-dependent variation in insecticidal toxicities; therefore an experiment was conducted during 2020–22 at ICAR-Indian Agricultural Research Institute, New Delhi, to study the host-specific toxicity relationships on tomato and brinjal using market-available safer insecticides with green labels in the Indian context. Bioefficacy evaluated on eggs, nymphs, and adults using leaf-dip bioassay (IRAC) recorded higher LC50 for candidate insecticides (clothianidin, spinetoram and cyantraniliprole), but lower toxicities for azadirachtin and novaluron for test-insects reared on brinjal. The possible role of test-leaf on LC50 was evaluated in a reciprocal way, i.e. test-populations grown in tomato were subjected to brinjal leaf bioassay and vice versa. This resulted to no significant change in LC50 and implies no effect of the test leaf. Feeding (honeydew excretion) and oviposition studies showed higher honeydew excretion (76.4 mm2) and egg-laying (43.6 eggs) per 20 adults on brinjal. Detoxification enzymatic activities in control showed the test enzymes, viz. carboxylesterase, glutathion S-transferase and cytochrome P450 monooxygenase, were at higher concentrations in the brinjal population, i.e. 1.75, 1.43 µ mol/min/mg, and 3.10 n mol/min/mg of protein. Results showed that brinjal is the preferred host for B. tabaci, on which it develops healthier and resulting in a higher insecticide dose to arrive at the desired lethal effect.